Ocena potencjalnej przydatności gleb murszastych Równiny Odrzańsko-Zalewowej jako siedliska leśnego z zastosowaniem indeksu trofizmu gleb leśnych = Assessment of potential usefulness of muck soils of the Odrzańsko-Zalewowa Plain as forest habitat with using of forest soil trophism index - Chudecka, Justyna; Sammel, Adam; Tomaszewicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to evaluate the potential usefulness of muck soils of the Odrzańsko-Zalewowa Plain, belonging to V class of arable land, as forest habitats with using of Forest Soil Trophism Index (ITGL). During the study period these soils were used in agriculture. According to bonitation classification, they corresponded to habitat of a mixed forest. According to typological classification and ITGL values, these soils were habitats of mixed forests and forests.
Keywords: zalesianie; gleby murszaste; indeks trofizmu gleb leśnych (ITGL); forestation; muck soils; forest soil trophism index (ITGL)